The Influence of Product Innovation and Product Quality on Competitive Advantage in IGI Bandar Lampung Eating Houses - Nur Alif Wijaya; Defrizal (PT FORMOSA CENDEKIA GLOBAL, 2024)
To support business growth and continuity, it is important to understand the influence of competitive advantage through product innovation and product quality. This research uses quantitative methods to explore competitive advantage which is influenced by product innovation and product quality implemented by IGI Restaurant. In this research, data was collected through surveys and statistical analysis to identify the relationship between product innovation and product quality on competitive advantage. The results of the quantitative analysis show that the innovation and product quality of IGI Restaurant have a positive impact on achieving competitive advantage with the regression coefficient value of product innovation on competitive advantage has a positive value. The regression coefficient value of the product quality variable on competitive advantage also has a positive value. This research provides strong quantitative support for the effectiveness of achieving competitive advantage through product innovation and product quality implemented by IGI Restaurant. These findings can be a basis for other culinary business players to make decisions in developing product innovation and product quality.